2016
DOI: 10.1016/j.ejvs.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Delays to Surgery and Procedural Risks Following Carotid Endarterectomy in the UK National Vascular Registry

Abstract: The delay from symptom to CEA in symptomatic patients with ipsilateral 50-99% carotid stenoses has reduced substantially, although 42% of patients underwent CEA after the recommended 14 days. The risk of stroke after CEA was low, but there may be a small increase in risk during the first 48 h after symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 31 publications
4
32
0
4
Order By: Relevance
“…Similar results could be found in multiple single‐center studies with the same limitations of low statistical power as the single‐center studies mentioned above . Two other secondary data analysis studies found an increased 30‐day risk for any stroke or death only if the surgery was performed within the first 2 days after the index event . Those differences from the German secondary data analysis study might be explained by different inclusion criteria: the Swedish and UK studies did not exclude emergency procedures such as crescendo TIA or stroke‐in‐evolution, which should be treated right after admission and are known to carry a higher risk of stroke or death .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results could be found in multiple single‐center studies with the same limitations of low statistical power as the single‐center studies mentioned above . Two other secondary data analysis studies found an increased 30‐day risk for any stroke or death only if the surgery was performed within the first 2 days after the index event . Those differences from the German secondary data analysis study might be explained by different inclusion criteria: the Swedish and UK studies did not exclude emergency procedures such as crescendo TIA or stroke‐in‐evolution, which should be treated right after admission and are known to carry a higher risk of stroke or death .…”
Section: Discussionsupporting
confidence: 72%
“…These patients would therefore be classified into the first time group (0‐2 days). Another explanation for the different findings could be the different end‐point definitions: the German study only assessed events until discharge, whereas the Swedish and UK studies assessed the 30‐day risks . However, how many strokes can be prevented by early treatment cannot be shown based on this secondary data analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Five studies reported the relationship using UK data sources 11,15,16,18,19,21 Nine studies [11][12][13][14][15][16][17][20][21][22] analysis of data collected as part of an administrative database.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of 23235 procedures in the UK 18 found no evidence of a relationship between the time from onset of symptoms to performance of CEA; over the five-year period of the study all hospitals improved their performance.…”
Section: Elapsed Time Between Symptoms and Cea: Hospital Volumementioning
confidence: 99%
“…National registry data from Sweden suggested that CEA or CAS performed within 48 h was associated with a high stroke/death risk of 11 per cent19. However, data from the UK20 and Germany21 showed only a minor increase in periprocedural risk associated with intervention within 48 h compared with 3–7 days. As a result of the CETC data, the treatment delay has decreased over recent years, from 22 days in 2009 to 12 days in 2013 in the UK, and from 28 days in 2003 to 8 days in 2014 in Germany.…”
mentioning
confidence: 99%